PREREQUISITES OF ADAPTIVE MANAGEMENT OF BUSINESS PROCESSESIN THE CONDITIONS OF DIGITALIZATION: THE NATIONAL DIMENSION - SHATALOVA, Liudmyla (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article defines the factors that form the environment of adaptive management of business processes in the conditions of digital transformation, and the nature of their influence. It was determined that the characteristic features of digital technologies are integration, intellectualization, and individualization. It is noted that the business process as a sequence of interrelated events that ensure the result of the activity of the subject of economic activity depends on many factors at each of the stages. It has been determined that the orientation of business processes on performance determines the objective necessity of classifying factors according to the nature of the impact - positive or negative. Among the favorable conditions, structural shifts in the labor market under the influence of digitalization, the formation of cyber-physical systems and platform technologies are highlighted. Structural shifts in the labor market under the influence of digitalization are associated with changes in labor relations, forms of employment, the quality of labor resources and their motivation, which will certainly contribute to changes in business models and their management. Cyber-physical systems, embodying material and virtual space, contribute to prompt response to problem situations, effective use of resources, and synchronization of work operations. Platform technologies help reduce transaction costs and save time. The threats of unfavorable factors are in the demographic and institutional planes and are related to deglobalization, resource failure. Unfortunately, it has been determined that the negative trends associated with the decrease in the number of labor resources and the deterioration of their quality characteristics will intensify. It is substantiated that in Ukraine at the current stage of development, the institutional environment does not have enough motivating motives for the effective use of the potential opportunities of business entities in the field of digitalization. It is noted that the resource failure is multi-layered and is a consequence of imperfect state regulation of the national economy, institutional environment, and low labor productivity. Prospects for further research are related to today's challenges and substantiation of the possibilities of using digital technologies in the construction of business models during the post-war reconstruction of our state.
Keywords: adaptive management; business process; digital technologies; factors influencing business processes; cyber physical system; platform technology